Element Modeling of Masonry Wall With Opening Under Lateral Force - Danna Darmayadi; Muhamad Rusli Ahyar (Universitas Islam Sultan Agung, 2018)
Abstract: Three-dimensional Finite Element Model for Masonry Wall with openings under lateral force using ABAQUS software. Finite element model verification with an experiment masonry wall in the laboratory without openings. The load-displacement relationship of finite element model is well agreed with experimental results. Parametric studies conducted on masonry wall with openings to investigate the influence of an area of openings. This research aimed to investigate the behavior of Masonry Walls with openings under lateral force. The result showed that the increase of the area of openings decreases stiffness and strength of masonry. It is also well observed from the result that lateral resistance of masonry will decrease for each area of the opening wall.